Social–cultural impacts of Bugis-Makassar diaspora in Malaysia (1666–1669) - Nahdia Nur; Mahadirin Hj. Ahmad; Taqdir Taqdir (Universitas Dian Nuswantoro, 2026)
This study investigates the Bugis–Makassar diaspora in Malaysia during 1666–1669 and its role in shaping socio-cultural relations in the Malay Peninsula. The research aims to identify the factors driving the migration, describe the settlement and interaction patterns that formed in the region, and analyze the long-term socio-cultural impacts of the diaspora. Using a qualitative method with a historical and descriptive-analytical approach, the study draws on primary sources such as colonial archives, historical documents, and manuscripts, supported by secondary sources including scholarly books and academic studies. Data were examined through heuristics, source criticism, interpretation, and historiography. The results show that the Bugis–Makassar diaspora developed extensive settlement and trade networks in major coastal centers such as Johor, Selangor, Kedah, and Riau. Their interactions with local Malay communities facilitated cultural exchange through intermarriage, shared traditions, and the emergence of hybrid identities. The diaspora also strengthened regional economic activity through maritime trade, resource management, and the transfer of navigational and craftsmanship knowledge. These processes produced lasting socio-cultural linkages between Indonesia and Malaysia, visible in shared cultural practices and intergenerational continuity within Bugis communities in Malaysia. The originality of this study lies in its comprehensive historical analysis that positions diaspora as a transformative socio-cultural force rather than a mere population movement, offering insights into the role of migration in shaping long-term regional connections in Southeast Asia.